Environmental and psychosocial barriers affect the active commuting to university in chilean students - Castillo Paredes, Antonio Jonathan.; Inostroza Jiménez, Natalia.; Parra Saldías, Maribel.; Palma Leal, Ximena.; Felipe, José Luis; Págola Aldazabal, Itziar.; Díaz Martínez, Ximena.; Rodríguez Rodríguez, Fernando. (Molecular Diversity Preservation International, 2021)
Biking and walking are active commuting, which is considered an opportunity to create healthy habits. Objective: The purpose of this study was to determine the main environmental and psychosocial barriers perceived by students, leading to less Active Commuting (AC) to university and to not reaching the Physical Activity (PA) recommendations. Material and Methods: In this crosssectional study, 1349 university students (637 men and 712 women) were selected. A self-reported questionnaire was applied to assess the mode of commuting, PA level and barriers to the use of the AC. Results: Women presented higher barriers associated with passive commuting than men. The main barriers for women were “involves too much planning” (OR: 5.25; 95% CI: 3.14–8.78), “It takes too much time” (OR: 4.62; 95% CI: 3.05–6.99) and “It takes too much physical effort “ (OR: 3.18; 95% CI: 2.05–4.94). In men, the main barriers were “It takes too much time” (OR: 4.22; 95% CI: 2.97–5.99), “involves too much planning” (OR: 2.49; 95% CI: 1.67–3.70) and “too much traffic along the route” (OR: 2.07; 95% CI: 1.47–2.93). Psychosocial barriers were found in both sexes. Conclusions: Psychosocial and personal barriers were more positively associated with passive commuting than environmental barriers. Interventions at the university are necessary to improve the perception of AC and encourage personal organization to travel more actively.
Keywords: Active; Commuting; Active transport; Physical activity; Active behavior; College